2018
DOI: 10.18011/bioeng2018v12n3p299-306
|View full text |Cite
|
Sign up to set email alerts
|

Produção De Mudas De Alface Em Resposta Ao Uso De Água Tratada Magneticamente

Abstract: Nos últimos anos tem sido crescente as pesquisas científicas de inovação e tecnologia agrícola a respeito da ação do campo magnético sob a germinação e desenvolvimento de plantas. Diante do exposto, esta pesquisa teve como objetivo avaliar o desenvolvimento inicial de mudas de alface (Lactuca Sativa L.) com uso de água tratada magneticamente e não tratada (controle). O experimento foi realizado em bandejas de 120 células, sendo a parcela constituída por 12 células com 10 repetições, onde foram testados os trat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Vieira et al (2020), working with the production of vegetable seedlings under seed magnetization and the use of magnetized water, found higher values for shoot dry mass for the treatment in which seedlings were irrigated with water treated with an Irrifes magnetizer (0.15 T). Pradela et al (2018), working with a Sylocimol Rural magnetizer, found a significant difference for shoot dry mass for the lettuce crop, the result being superior for the treatment using magnetization. The different magnetization levels used in seed treatment and irrigation did not affect the seed vigor variable at the 5% level (Table 9).…”
Section: Days After Seedingmentioning
confidence: 96%
“…Vieira et al (2020), working with the production of vegetable seedlings under seed magnetization and the use of magnetized water, found higher values for shoot dry mass for the treatment in which seedlings were irrigated with water treated with an Irrifes magnetizer (0.15 T). Pradela et al (2018), working with a Sylocimol Rural magnetizer, found a significant difference for shoot dry mass for the lettuce crop, the result being superior for the treatment using magnetization. The different magnetization levels used in seed treatment and irrigation did not affect the seed vigor variable at the 5% level (Table 9).…”
Section: Days After Seedingmentioning
confidence: 96%